Diabetic induced mice treated with olive leaves (Olea europaea) aqueous extract - AlBadri, Cinaria T.; Al-Ani, Imad Matloub Dally (2011)
Due to the widespread prevalence of diabetes and the severity of complication, extensive research are underway to find more effective remedies to improve the life of those affected by the disease. Diabetes mellitus is chronic disease caused by inhered and/or acquired deficiency in production of insulin by the pancreas which results in increase concentration of blood glucose level (1).The objectives of this study were to investigate the effects of the aqueous extract of Olea europaea on serum glucose level and histopathological changes in islets of Langerhans in an induced-diabetic mellitus in mice (2, 3). Animals were anaesthetized by diethyl ether after fasting for up to 13 hours and on day 7, 14, 21 and 28 the blood specimens were collected and the serum separated. Serum glucose levels were determined by the glucose oxidase method. The pancreas was excised, ﬁxed in the Boon’s solution and processed for histological studies. The results showed that administration of the aqueous extract exhibited a signiﬁcant increase in the average size of islets of Langerhans of the streptozotocin diabetic animals, while the treatment with Olea europaea aqueous extract showed a marked reduction in the islet size. 1.Sexton WJ, Jarow JP. J.Urology, 1997; 49: 508-515. 2.Hardman JG, Limbird LE. The Pharmacological basis of Therapeutics. 10th Ed. New York. 2011; P 1399. 3.Weir GC, Clore ET, Zmachinski CJ, Bonner-Weir S. Diabetes. 1981; 30: 590-595.